From enclosed domestic labour to training centers: challenges of the union and the NGOs in organizing paid child domestic workers in Tanzania - Kapinga, Silpha (My University, 2009)
ABSTRACT The challenges surrounding organizing of paid child domestic workers have been relatively under-explored. This study is about the strategies and challenges of the union (CHODAWU) and the NGO (KIWOHEDE) in organizing paid child domestic workers in Tanzania. The study attempts to analyse the institution of paid domestic work, in particular paid child domestic work. In many countries, domestic service has been predominantly done by adult domestic workers, quite often foreign immigrants or intra-imigrants from rural areas to urban centers. In Tanzania the situation is quite different. The dominant work force in domestic service are children often with very low or basic primary education, a majority of whom come from poor rural families. Experience has shown that organizing of such child domestics is challenging. The trade union (CHODAWU) and the NGO (KIWOHEDE) have tried to organize paid child domestics without any tangible progress. This study attempted to assess the roles and strategies that the NGOs and unions use in organising paid child domestic workers. It also examines the different challenges facing both the NGOs and the unions in organising paid child domestics. The field interviews were conducted with the Union 2008 in Dar es Salaam city, the capital city of Tanzania. In terms of the research methodology, the study used both primary and secondary sources of data collection. The field research was conducted to the officials of the two selected organisations KIWOHEDE (NGO) and CHODAWU ( local union) in Dar es salaam city. Among other things the study found that despite their differences in structures, composition, goals and roles, both the union and the NGO use similar strategies in organising paid child domestic workers. i.e they use provision of vocational skills and training as the means to reach and interact with the domestic workers. It was also found that there is no clear and unified legal position on the definition of a child domestic worker as well as on the employment status of the same. This legal ambiguity creates one of the more potent challenges for organising.